2001
DOI: 10.1207/s1532799xssr0501_3
|View full text |Cite
|
Sign up to set email alerts
|

Language Phenotype for Reading and Writing Disability: A Family Approach

Abstract: A theory-driven battery of 23 psychometric measures of reading, writing, and related language processes was administered to 102 probands (affected children in Grades 1 to 6 with documented reading problems, writing problems, or both) and both of their biological parents. Affected children and parents were compared on the structural relationships between related language processes (Verbal IQ [VIQ], orthographic, phonological, and rapid naming skills), component reading, (accuracy, rate, comprehension) and writi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 82 publications
(62 reference statements)
3
133
0
3
Order By: Relevance
“…4,45 Under a protocol approved by the Institutional Review Board of the University of Washington, families were initially identified through school age children with reading difficulties. Individuals were included if they met the following criteria, based on scores from 10 specific qualifying tests in a battery of 23 tests plus an IQ test administered by the research team.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…4,45 Under a protocol approved by the Institutional Review Board of the University of Washington, families were initially identified through school age children with reading difficulties. Individuals were included if they met the following criteria, based on scores from 10 specific qualifying tests in a battery of 23 tests plus an IQ test administered by the research team.…”
Section: Subjectsmentioning
confidence: 99%
“…The test battery is described elsewhere. 4,45 Probands had to have a prorated verbal IQ (VIQ) Z90 (Z25%ile) on the Wechsler Intelligence Scale for Children-3rd Edition, 46 and score below the population mean and at least 1 standard deviation below their VIQ on at least one of 10 of the measures of accuracy and speed of single real or nonword reading, accuracy or rate of oral reading of text, spelling, or handwriting automaticity. In fact, most probands were impaired on most or all of the 10 measures.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies confirm LDs are inherited, though they agree that their course can be determined by environmental variables. They point towards the influence of purely educational factors, such as the role of teachers, the teaching method or procedures followed, as well as family variables related to home provision of resources, parental level of education or the family's socioeconomic situation (Berninger, Abbott & Thompson, 2001;Lyytinen, Eklund, & Lyytinen, 2005;Monuteaux, Faraone, Herzig, Navsaria, & Biederman, 2005;Shalev, et al, 2001;Snowling, et al, 2007). The thesis that despite the LD being part of the individual there is a high influence of environmental aspects on its course and severity is further reinforced by these studies.…”
Section: General Studies On Ld and Familiesmentioning
confidence: 99%